Medical terminology : - Willis, Marjorie Canfield (Williams & Wilkins, 1996)
Now students can learn medical terminology in its proper context—in documenting patient care. The text teaches students APPLIED terminology, demonstrating exactly how medical terminology is used in the clinical practice setting. Willis’ Medical Terminology features COMPLETE records with patient history included. Completely unique, the fourth chapter teaches basic communication between professionals, including physician’s orders and prescriptions, plus..."Ancient Artifacts" with colorful etymologies and historical backgrounds for commonly used terms.